Volume-based Interval Training Program for Elite Tennis Players - Myers, Natalie L. (Sports Health, 2016)
BACKGROUND: A sport-specific conditioning program can help tennis players train for competition or return to play from injury. This study determined the actual tennis serve volume in elite play and used these data to construct an interval training program based on stroke volume. HYPOTHESIS: There will be no differences in serve volume between male and female tennis players at the professional and junior levels. STUDY DESIGN: Retrospective cohort study. LEVEL OF EVIDENCE: Level 3. METHODS: Game day statistic scorecards were provided to the research team from the 2013 and 2014 United States Open and the 2014 Metropolia Orange Bowl International Tennis Championships. Serve volume data for both male and female players were extracted from the scorecards. Data included serves per match and per set. These data were used to construct a sport-specific tennis program to meet the demands of the serve. RESULTS: Professional male players serve 63 more serves per match than junior male players because of the greater number of sets played (P < 0.01). Professional female players serve 10 more serves per match than junior female players playing the same number of sets (P = 0.01). All male players hit 2 more total serves per set than all female players (P < 0.01). Regardless of sex, professional players serve 4 more serves per set than junior players (P < 0.01). The typical number of serves per set was 40 in elite-level tennis players, resulting in a 3:1 ratio of first to second serves. CONCLUSION: These data establish the “unit dose” of serves per match and/or per set for each group. CLINICAL RELEVANCE: Coaches and health care providers may use these data in estimating loads per tournament/season and to prepare tennis athletes for individual competition and/or as they return to play after an injury.